Public engagement in Malawi through a health-talk radio programme 'Umoyo nkukambirana': A mixed-methods evaluation. (February 2018) - Nyirenda, Deborah; Makawa, Tamara Chipasula; Chapita, Greyson; Mdalla, Chisomo; Nkolokosa, Mzati; O'byrne, Thomasena; Heyderman, Robert; Desmond, Nicola
Radio is an effective source of health information in many resource poor countries. In Malawi, 53% of households own radios however few radio programmes in Malawi focus on health issues in the context of medical research. An interactive health-talk radio programme ' Umoyo nkukambirana ' was introduced by Malawi-Liverpool-Wellcome Trust Clinical Research Programme on a national radio station. The aim was to increase awareness of health and medical research, and improve engagement between researchers, healthcare workers and the public. The content and presentation were developed through participatory community consultations. Focus Group Discussions were conducted with established Radio Listening Clubs whilst quantitative data was collected using toll free FrontlineSMS to explore national response. A total of 277 to 695 SMS (Median: 477) were received per theme. The majority of SMS were received from men (64%) and mainly from rural areas (54%). The programme improved knowledge of medical research, health and dispelled misconceptions. This study suggests that the radio may be an effective means of increasing the exposure of men to health information in resource poor settings.